LIBOR Discontinuation and the Cost of Bank Loans - Kim, Jeong-Bon; Wang, Chong; Wu, Feng (Harry) (Management Science, 2025)
With the London Interbank Offered Rate (LIBOR) being replaced by risk-free rate (RFR)-based alternative reference rates, the fundamental differences between the two benchmarking frameworks impose significant risks on banks. Exploiting the Financial Conduct Authority (FCA)’s announcement of the phase-out of LIBOR, we conduct a difference-in-differences analysis based on banks’ reliance on LIBOR and show that LIBOR discontinuation entails higher interest rate spread of bank loans. The result implies that banks tend to compensate for the LIBOR-to-RFR risks by passing on the transition costs to borrowers. This effect is attenuated if multiple benchmarks are already in use, for relationship lending, and among banks operating in a competitive environment. We further find that LIBOR discontinuation leads to more collateral and covenant requirements in loan terms. After the FCA announcement, banks are inclined to switch away from LIBOR dependence by referencing alternative rates. This paper was accepted by Victoria Ivashina, finance. Funding: J.-B. Kim acknowledges support from City University of Hong Kong; C. Wang acknowledges support from Hong Kong Polytechnic University and the National Natural Science Foundation of China [No. 71932003]; F. (H.) Wu acknowledges support from the General Research Fund [No. 13500820] from the University Grants Committee of Hong Kong. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.03133 .